Evaluation of Public Open Space Based on Crime Prevention Through Environmental Design (CPTED) at Baturaja City Park, South Sumatera, Indonesia - Leonardo Margen Snapal; Rizka Nabilah (Sinektika: Jurnal Arsitektur, 2026)
Public open spaces (POS) play a critical role in supporting the social, ecological, and economic sustainability of urban areas. However, their functions are often compromised by criminal activities and inadequate safety provisions. This study evaluates the management of Baturaja City Park, a public open space in Ogan Komering Ulu Regency, South Sumatera, Indonesia, using the Crime Prevention Through Environmental Design (CPTED) framework. Employing a mixed-method approach combining qualitative field observation, structured expert questionnaires, Analytical Hierarchy Process (AHP) for variable weighting, and SWOT matrix analysis for strategic evaluation the research systematically assessed biophysical, utility, activity, security, and management aspects of the park. Field observations were conducted over seven days (4–10 August 2025). Three expert respondents from the Local Housing and Settlement Office (Dinas PERKIM OKU) provided weighted assessments. Results reveal significant deficiencies in natural surveillance due to non-functional lighting systems, absence of CCTV, inadequate security personnel, limited evacuation routes, and overgrown vegetation obstructing sightlines. The SWOT-AHP analysis positioned the park in Quadrant I (Growth Strategy), with internal strength score (S=1.23) marginally exceeding weakness (W=1.21) and opportunity (O=1.36) surpassing threat (T=0.95). The study produced comprehensive design and management recommendations aligned with four CPTED principles: natural surveillance, territorial reinforcement, natural access control, and maintenance/management. Key recommendations include installation of 92 surveillance cameras (including smart CCTV), 396 lighting units across three typologies, redesign of access points, vegetation management, and digital maintenance reporting systems.